Distribución del gasto del programa en asistencia solidaria pensión 65 por regiones del Perú periodo 2020-2024 - Moncada Icahuate, Valeria (2025)
Social programs in Peru and Latin America are essential to reduce inequalities, promote inclusion and social cohesion, although they face structural challenges that require greater knowledge and adjustments to maximize their impact, this study aims to identify how the distribution of spending on the pension 65 solidarity assistance program is presented by regions of Peru period 2020 2024., with a quantitative observational approach and a non-experimental design, considering a population made up of official budgetary financial data executed within the pension 65 program, the analysis shows that the distribution of program spending presents persistent inequalities between regions throughout the period, Cajamarca, Puno and Piura concentrate a greater part of the funds, while Madre de Dios, Tacna and Moquegua register the lowest percentages, likewise, the source of financing is based almost exclusively on Ordinary Resources, exceeding 99% of the allocation in most years, which shows a high budgetary dependence, in terms of the expenditure structure, it is noted that the category "Other Expenses" far exceeds the others, accounting for more than 90% of total expenditure. However, overall investment shows a positive and growing trend, rising from 878 million soles in 2020 to 1.29 billion soles in 2024, indicating a sustained effort to strengthen the program. The findings confirm that, despite the budget expansion, significant allocation gaps persist, suggesting the need for a more robust approach to targeting and financial equity for its effective implementation.